2017
DOI: 10.1186/s12906-017-1846-5
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effects of Xinji′erkang on myocardial infarction induced cardiac injury in mice

Abstract: BackgroundMyocardial infarction (MI) is a major risk factor responsible for morbidity and mortality. Xinji′erkang (XJEK) has been clinically used as an effective medication in the treatment of coronary heart disease and myocarditis. The purpose of this study was to investigate the cardioprotective effect of Xinji′erkang on MI mice.MethodsForty male mice were randomly assigned into four groups as follows (n = 10): sham, model, MI with administration of XJEK and fosinopril for four weeks. At the end of studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…It has also been demonstrated that boosted Treg function ameliorates Ang II and aldosterone-induced hypertension, cardiac fibrosis, coronary inflammation, electrical remodeling and impaired endothelial-dependent vasodilatation, which are possibly mediated at least partially by IL-10 release from Tregs (50). Previous studies (32,51) have confirmed the key role of the balance between pro- and anti-inflammatory cytokines in cardiovascular remodeling and ED that often accompany hypertension, and restoring of this balance is crucial in the prevention of cardiovascular damage. Based on these findings, the present study demonstrated the presence of an immunological imbalance exists in the high salt-induced hypertensive mouse model, reflected by an increase in TNF-α and IL-1β and a decrease in IL-10 levels.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It has also been demonstrated that boosted Treg function ameliorates Ang II and aldosterone-induced hypertension, cardiac fibrosis, coronary inflammation, electrical remodeling and impaired endothelial-dependent vasodilatation, which are possibly mediated at least partially by IL-10 release from Tregs (50). Previous studies (32,51) have confirmed the key role of the balance between pro- and anti-inflammatory cytokines in cardiovascular remodeling and ED that often accompany hypertension, and restoring of this balance is crucial in the prevention of cardiovascular damage. Based on these findings, the present study demonstrated the presence of an immunological imbalance exists in the high salt-induced hypertensive mouse model, reflected by an increase in TNF-α and IL-1β and a decrease in IL-10 levels.…”
Section: Discussionmentioning
confidence: 79%
“…The dose of XJEK for the present study was based on the clinical dose, and was converted for mice according to pharmacology conversion formula (30). Furthermore, the dose of XJEK was considered based on our previous report (31,32) and with minor modifications according to different animal models.…”
Section: Discussionmentioning
confidence: 99%
“…All pregnant mice were anesthetized with pentobarbital sodium (45 mg/kg, ip ) at the end of 3 weeks, then the neck was dissected, and the right common carotid artery isolated and cannulated with a polyethylene catheter connected to a Statham transducer. The carotid artery pressure was measured; afterwards the signals were recorded and analyzed on a four channel direct‐writing oscillograph (BL420S; Chengdu Techman Software Co. Ltd.) and digitally sampled (1 kHz) on a personal computer equipped with an analogue to digital interface (BL420S biological function experiment system) and analyzed as previously described (Hu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Chengdu Techman Software Co. Ltd.) and digitally sampled (1 kHz) on a personal computer equipped with an analogue to digital interface (BL420S biological function experiment system) and analyzed as previously described (Hu et al, 2017).…”
Section: Measurement Of Artery Systolic Blood Pressurementioning
confidence: 99%
“…Coronary artery disease (CAD) is a worldwide health problem that very often leads to myocardial infarction (MI). In fact, MI, an acute condition of necrosis of myocardium is the most lethal manifestation of CAD that normally results when blood flow stops to a part of the heart, causing damage to the heart muscles 1 . This can be studied by examining the changes in different patho-physiological indices including electrocardiogram (ECG), serum levels of troponin-I, cardiac enzyme markers, and by imaging cardiac tissues 2 .…”
Section: Introductionmentioning
confidence: 99%